Dining comfort in elderly care facility dining rooms and influencing factors before and after the outbreak of the COVID-19 pandemic - Mu, Jingyi; Kang, Jian (Frontiers in Psychology, 2023)
Introduction The COVID-19 pandemic has changed dining modes in elderly care facilities. This study explores the relationship between the dining environment of four elderly care facilities and the sensitivity of the elderly residents to it before and after the outbreak of the COVID-19 pandemic. Methods The study examined differences in subjective comfort levels by measuring the facilities’ physical environment, analysing dining behavior, and surveying the elderly residents. And the study examined how the interaction between the physical environment factors, demographic factors, and dining mode affected the residents’ evaluation of their dining comfort. Results (1) The physical environmental parameters of the four dining rooms differed between the pre- and post-epidemic periods, as shown by increased Sound Pressure Level (SPL), humidity, and temperature levels. (2) The residents’ evaluations of physical environment comfort also changed after the outbreak of the COVID-19 pandemic. The subjective comfort levels of the ‘dining with baffle’ and ‘dining across a seat’ modes decreased, though the level of the former was slightly higher than that of the latter. The elderly had stronger SPL tolerance in the dining with baffle mode and dining across a seat mode, and their subjective comfort levels for thermal environment and air quality were higher in the dining across a seat mode. (3) When dining time, crowd density, and communication frequency were kept equal, the subjective comfort level of the elderly in the dining with baffle mode and dining across a seat mode was lower than that in the ‘normal’ dining mode, when the level in the dining with baffle mode was lower than that in the dining across a seat mode. (4) Differences were observed in subjective comfort levels according to age, education level, and residence duration across the dining modes. Discussion The need for changes in dining modes during the COVID-19 isolation period require dining rooms in elderly care facilities to design their physical environments in a way that improves dining comfort for the elderly.